The Logic Disseminated by the Mainstream: A Study With Individuals That Work Within Hip Hop Movement - Bispo, Danielle de Araújo; Paschoal Dourado, Débora Coutinho; Loureiro Amorim, Mariana Fernandes da Cunha (Organizações & Sociedade, 2014)
This article explores the meaning that individuals involved with the Hip Hop attach to their work. The theoretical framework explores the meanings that work has acquired through history, especially in contemporaneity. A qualitative approach for investigation was adopted, with oral history as the major method of research. The selection of interviewees was based on the key informants’ criterion. The data was analyzed through content analysis. Results obtained from this analysis were compared with the ethos developed by Bendassoli (2007; 2009) about the meaning of work in contemporary society. The conclusion reached was that the meaning of work for the respondents is based on a romantic-expressive ethos. It is important to clarify that throughout life these individuals experienced or were exposed to more than one ethos.